2016
DOI: 10.1112/s0010437x16007296
|View full text |Cite
|
Sign up to set email alerts
|

Dense clusters of primes in subsets

Abstract: Abstract. We prove a generalization of the author's work to show that any subset of the primes which is 'well-distributed' in arithmetic progressions contains many primes which are close together. Moreover, our bounds hold with some uniformity in the parameters. As applications, we show there are infinitely many intervals of length (log x) ǫ containing ≫ ǫ log log x primes, and show lower bounds of the correct order of magnitude for the number of strings of m congruent primes with p n+m − p n ≤ ǫ log x.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
145
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(152 citation statements)
references
References 19 publications
(61 reference statements)
6
145
0
Order By: Relevance
“…We may assume that x is suf-http://www.resmathsci.com/content/1/1/12 ficiently large depending on all fixed quantities. By (16), the left-hand side of (29) may be expanded as…”
Section: The Trivial Casementioning
confidence: 99%
See 1 more Smart Citation
“…We may assume that x is suf-http://www.resmathsci.com/content/1/1/12 ficiently large depending on all fixed quantities. By (16), the left-hand side of (29) may be expanded as…”
Section: The Trivial Casementioning
confidence: 99%
“…For the sake of notation, we take i 0 = k, as the other cases are similar. We use (16) to rewrite the left-hand side of (26) as…”
Section: The Elliott-halberstam Casementioning
confidence: 99%
“…In the direction of these conjectures, the earliest work we found is the paper of Knapowski and Turán (3), who "guess" that the events p n ≡ a ðmod 4Þ and p n+1 ≡ b ðmod 4Þ for the four possibilities of a and b are "not equally probable." However, Knapowski and Turán go on to suggest that πðx; 4; ð1; 1ÞÞ = oðπðxÞÞ, which is now definitively false by Maynard's work (6). The paper (3) was published after the death of both authors, and perhaps they had something else in mind, maybe along the lines of our Conjecture 1.2 above?…”
Section: Significancementioning
confidence: 97%
“…Recent progress in sieve theory has led to a new proof of Shiu's result (see ref. 5), and, moreover, Maynard (6) has shown that πðx; q; ða; . .…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of literature has addressed the structure of these sequences, some relevant references include [20][21][22][23][24]. Gaps between primes (ever odd except for the number 2 and 3 the only gap with g = 1)…”
Section: Introductionmentioning
confidence: 99%